2005
DOI: 10.1007/s10620-005-2764-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Eradication of Helicobacter pylori Infection Help Normalize Serum Lipid and CRP Levels?

Abstract: It is still unclear whether Helicobacter pylori infection is associated with risk factors for coronary artery disease. The aim of this study was to determine whether eradication of H. pylori infection affects serum lipid levels and C-reactive protein (CRP) levels. Seventy-eight patients who had H. pylori antigen positivity in their stools were enrolled. Clarithromycin, 1 g/day, amoxicillin, 2 g/day, and omeprazole, 40 mg/day, were given for 14 days. Serum total cholesterol (TC), high-density lipoprotein (HDL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 18 publications
8
65
2
3
Order By: Relevance
“…Furthermore, numerous studies have demonstrated that chronic H. pylori infection upregulates the serum CRP level 88,89) , and the high-sensitivity CRP (hsCRP) levels have been reported to be significantly higher in H. pylori-infected individuals, especially those with CagApositive infection, consistent with the strong correlation between infection with more virulent H. pylori strains and atherosclerosis 78,90) . The effects of H. pylori infection on the CRP level are further corroborated by the observation of a significant reduction in the serum CRP level after H. pylori eradication 79) . CRP may elicit a wide array of pro-atherogenic effects, including the stimulation of leukocyte-endothelium interactions, induction of a prothrombotic state and activation of the complement system 91) .…”
Section: H Pylori Related-inflammation and Atherosclerosismentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, numerous studies have demonstrated that chronic H. pylori infection upregulates the serum CRP level 88,89) , and the high-sensitivity CRP (hsCRP) levels have been reported to be significantly higher in H. pylori-infected individuals, especially those with CagApositive infection, consistent with the strong correlation between infection with more virulent H. pylori strains and atherosclerosis 78,90) . The effects of H. pylori infection on the CRP level are further corroborated by the observation of a significant reduction in the serum CRP level after H. pylori eradication 79) . CRP may elicit a wide array of pro-atherogenic effects, including the stimulation of leukocyte-endothelium interactions, induction of a prothrombotic state and activation of the complement system 91) .…”
Section: H Pylori Related-inflammation and Atherosclerosismentioning
confidence: 72%
“…Clinical investigations have confirmed correlations between circulating markers of inflammation, such as C-reactive protein (CRP) 28,71,72) , tumor necrosis factor (TNF) 73,74) , interleukin (IL)-6 71,75) and IL-18 76,77) , and the occurrence of atherosclerosis and its cerebrovascular or cardiovascular events. In addition, growing evidence suggests that H. pylori infection, accompanied by persistent low-grade systematic inflammation, contributes to the risk of atherosclerosis by stimulating the production of proinflammatory cytokines, such as CRP 78,79) , IL-6 80) , and IL-18 81) , all of which are predictors of atherosclerosis.…”
Section: H Pylori Related-inflammation and Atherosclerosismentioning
confidence: 99%
“…Aslan et al (17) and Sung et al (16) reported that serum TG, TC and LDL-C levels in HP seropositive subjects were significantly higher than in HP seronegative ones (all p<0.05). In a study of Kanbay et al (20), normalization in lipid parameters after a successful eradication of HP infection was observed. Majka et al (4) and Kucukazman et al (18) found that plasma levels of TC and LDL-C were significantly higher in HP seropositive subjects, and after 6 months of successful anti-HP therapy those levels were significantly lowered (4).…”
Section: Discussionmentioning
confidence: 92%
“…Although most authors reported about an association between HP infection and a proatherogenic lipid profile (6,(16)(17)(18)(19) which was normalized after successful eradication of HP (4,20), few studies did not confirm these results (1,2,5,10,21). Therefore, the influence of chronic HP infection on lipid parameter changes and their implication in atherogenic mechanisms of this infection are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The mean fasting insulin, HOMA-IR, total cholesterol (TC), TG, LDL-C, CRP levels and HDL-C levels in patients with unsuccessful eradication were not significantly changed from pretreatment levels [20]. Other studies also showed positive lipid profile changes and inflammatory marker decrease [21].…”
Section: Metabolic Changes In Hp With T2dmmentioning
confidence: 95%